The influence of freezing-thawing cycles on the capillary water absorption and porosity of concrete with mineral admixture - Gonen, Tahir; Yazicioglu, Salih; Demirel, Bahar (Korean Society of Civil Engineers-Ksce, 2015)
The main objective of this experimental study is to determine which of the effective parameter among ultrasonic pulse velocity, compressive strength, capillary water absorption and porosity during freezing and thawing on concrete produced with mineral admixtures. The specimens were exposed to 25, 50, 75 and 100 freezing-thawing cycles after 28 curing days. The results showed that among the measured parameters, capillary water absorption was the most affected parameter from freeze-thaw cycles.
Keywords: capillary water absorption; freezing-thawing; mineral admixture; porosity; ultrasonic pulse velocity